1996
DOI: 10.1016/s0022-5223(96)70261-1
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and survival after operations for primary lung cancer from 1976 through 1990

Abstract: To assess the time trends and survivals after operations for primary lung cancer, the cases of 845 consecutive patients who underwent thoracotomy between 1976 and 1990 were retrospectively reviewed by groups corresponding to year of the operation (the early period was 1976 to 1980, n = 208; the middle period was 1981 to 1985, n = 291, and the late period was 1986 to 1990, n = 346). The 5-year survivals at the early, the middle, and the late periods were 31.5%, 39.0%, and 54.0%, respectively, with significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 10 publications
2
23
0
1
Order By: Relevance
“…As postoperative adjuvant therapy, 13 patients received intravenous chemotherapy, seven received oral administration of UFT, a 5-fluorouracil derivative chemotherapeutic agent, and one received both; the other 97 patients received no therapy postoperatively. Complete tumor resection was considered to have been achieved when no microscopic cancer was identified in either the margin of resection of the tumor or the highest mediastinal lymph nodes [24]. Pathologic stage was determined according to the tumor-node metastasis (TNM) classification as revised in 1997 [2].…”
Section: Introductionmentioning
confidence: 99%
“…As postoperative adjuvant therapy, 13 patients received intravenous chemotherapy, seven received oral administration of UFT, a 5-fluorouracil derivative chemotherapeutic agent, and one received both; the other 97 patients received no therapy postoperatively. Complete tumor resection was considered to have been achieved when no microscopic cancer was identified in either the margin of resection of the tumor or the highest mediastinal lymph nodes [24]. Pathologic stage was determined according to the tumor-node metastasis (TNM) classification as revised in 1997 [2].…”
Section: Introductionmentioning
confidence: 99%
“…radical surgery, has remained the same, but the surgical techniques and postoperative treatments have improved. Clinical studies addressing the effects of chemotherapy and combination therapy, especially in small cell carcinoma and stage III disease have suggested that they prolong survival [3][4][5]. Many of these studies have, however, been conducted in centres with a particular interest in chemotherapy and in groups of patients with strictly defined inclusion criteria.…”
mentioning
confidence: 99%
“…They found that the group who had received UFT showed a significantly better prognosis than the group who had not. However, in these two reports, 26,27 it was not clear why UFT was effective when used for postoperative adjuvant chemotherapy in patients with NSCLC. Thus, within the limits of conjecture, it is possible that UFT targets the micro-metastatic lesions of lymph nodes 28 in patients with p-N0 NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…Wada et al 27 examined the 5-year survival rate of patients with p-N0 NSCLC to whom UFT was administered as an additional postoperative adjuvant chemotherapy after complete resection and initial postoperative adjuvant chemotherapy with PVM (cisplatin ϩ vindesine ϩ mitomycin C). They found that the group who had received UFT showed a significantly better prognosis than the group who had not.…”
Section: Discussionmentioning
confidence: 99%